# How do you differentiate #f(x)=(x^2+x)(x^3-1)# using the product rule?

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate ( f(x) = (x^2+x)(x^3-1) ) using the product rule, you would use the formula ( (uv)' = u'v + uv' ), where ( u = x^2 + x ) and ( v = x^3 - 1 ).

First, find ( u' ) and ( v' ):

( u' = \frac{d}{dx}(x^2 + x) = 2x + 1 )

( v' = \frac{d}{dx}(x^3 - 1) = 3x^2 )

Now, apply the product rule:

( f'(x) = (2x+1)(x^3-1) + (x^2+x)(3x^2) )

Simplify:

( f'(x) = 2x^3 - 2x + 3x^4 - 3x^2 + 3x^4 + 3x^3 )

Combine like terms:

( f'(x) = 6x^4 + 5x^3 - 5x^2 - 2x )

So, ( f'(x) = 6x^4 + 5x^3 - 5x^2 - 2x ) is the derivative of ( f(x) = (x^2+x)(x^3-1) ) using the product rule.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you differentiate #f(x)=(3x-cos^3x)^2/4# using the chain rule?
- How do you differentiate #y = (2x^4 - 3x) / (4x - 1)#?
- How do you differentiate #y=5x^3(sinx)^2#?
- How do you find #dy/dx# by implicit differentiation of #x^3+y^3=4xy+1# and evaluate at point (2,1)?
- How do you implicitly differentiate #11=(x-y)/(e^y-e^x)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7